Mirrors of Stone: Fragments from the Porcupine Frontier - Angus, Charlie; Palu, Louie (Between the Lines, 2001)
Mirrors of Stone delves into the many ethnic cultures that thrived in the mining areas of Northern Ontario from the 1920s to the 1960s. The stormy history of hardrock mining camps has never fit into the comfortable cliches by which Canada “tells its story.” Angus unearths the dark sides of this history–“the wild tales of bootleggers, mobsters, and prostitution rings” and in so doing opens up new ways of seeing Ontario’s history and culture. --Publisher's description

Building a Better World: An Introduction to Trade Unionism in Canada - Black, Errol; Silver, Jim (Fernwood, 2001)
This introductory text examines the vital role of trade unions in Canada. In particular, it emphasizes how the values. objectives and activities of unions are shaped and changed in the context of employer opposition and often hostile governments. --Publisher's description.
Keywords: Labor unions -- Canada

Framing Our Past: Canadian Women's History in the Twentieth Century - Cook, Sharon Anne; McLean, Lorna; O'Rourke, Kate (McGill-Queen's University Press, 2001)
Framing Our Past is about women's lived experience. Drawing from diaries, oral history, letters, organizational records, paintings, quilts, dressmaking patterns, milliners' records, and posters, the contributors offer fresh interpretations of this historical material and unique insights into the lives of individual Canadian women who expanded the boundaries of traditional roles. Lavishly illustrated, Framing Our Past looks at women and their social rituals with other women, organized sporting clubs, philanthropic, spiritual and aesthetic activities, study and reading groups. The authors explore women's roles as nurturers and keepers of the hearth and in family management, child care, and health care. They highlight women's work in areas as diverse as domestic labour, nursing, dressmaking, broadcasting, and banking as well as women's contributions to education and their instrumental political role in consumer activism, social work, and peace movements. --Publisher's description
Keywords: Women -- Canada -- History -- 20th century

La pensée de Gustave Francq, syndicaliste et réformateur social : textes choisis, 1905-1948 - Francq, Gustave; Leroux, Éric (Collection RCHTQ, 2001)
Keywords: 1900-1999; Canada; Francq, Gustave, 1871-1952 Pensée politique et sociale; Francq, Gustave, Political and social view; History; Labor unions; Labor unions Canada History 20th century; Québec; Québec (Province) Conditions sociales 20e siècle; Québec (Province) Social conditions 20th century; Social conditions; Syndicalism; Syndicalism Québec (Province) History; Syndicalisme Québec (Province) Histoire; Syndicats Canada Histoire 20e siècle

Labour Before the Law: The Regulation of Workers' Collective Action in Canada, 1900-1948 - Fudge, Judy; Tucker, Eric (Canadian social history series, 2001)
In this study of the relations between workers and the state, Judy Fudge and Eric Tucker examine the legal regulation of workers' collective action from 1900 to 1948. They analyze the strikes, violent confrontations, lockouts, union organizing drives, legislative initiatives, and major judicial decisions that transformed the labour relations regime of liberal voluntarism, which prevailed in the later part of the nineteenth century, into industrial voluntarism, whose centrepiece was Mackenzie King's Industrial Disputes Investigation Act of 1907. This period was marked by coercion and compromise, as workers organized and fought to extend their rights against the profit-oriented owners of capital, while the state struggled to define a labour regime that contained industrial conflict. The authors then trace the conflicts that eventually produced the industrial pluralism that Canadians have known in more recent years." "The book is simultaneously & history of law, aspects of the state, trade unions and labouring people, and their interaction within the broad and shifting terrain of political economy. The authors are attentive to regional differences and sectoral divergences, and they attempt to address the fragmentation of class experience. -- Publisher's description
Keywords: 20e siecle. Travail; 20th century. Syndicats; Canada; Droit; Histoire; History; Labor Unions; Law and legislation

A Very Red Life: The Story of Bill Walsh - Gonick, Cy (Past CCLH Publications, 2001)
Montreal-born Moishe Wolofsky was a nineteen year-old unemployed university drop-out in 1930 when he and his friend Dick Steele took a job aboard an ocean vessel, beginning a journey that would change his life forever. Out of money, they stumbled into Russia and took jobs in a tractor factory. There, they became dedicated communists. Dragged back to Canada by his father, the well-known Jewish publisher, Herschel Wolofsky, he soon began a career as an organizer for the Communist Party of Canada. By then Moishe Wolofsky had become Bill Walsh. Still a very young man, he led the drive to organize the rubber workers in Kitchener and subsequently the auto workers in Windsor. Jailed and interned along with several hundred other Communists, upon his release Walsh fought overseas in Holland and Belgium. After the war he took a staff position with the United Electrical Workers in Hamilton, a job he retained for over two decades. After years of conflict with UE President C.S. Jackson, Walsh was forced to quit his job and subsequently the Communist Party. In the late 60s, he began a new career in labour arbitration. This is the story of how a young idealist became a Red and helped build industrial unionism in Canada. But it is also a story of romance and adventure. Walsh actively participated in many of the 20th century's historic events. Everything he did was touched with an intensity. He was a brilliant strategist and an extraordinary teacher. Because he never held high office either in politics, in uniform, or in any of the unions he was associated with, his contributions have gone unheralded. This book provides an inside, bottom-up look at some of the most important episodes in our trade union history as well as an insight into the functioning of a venerable communist-led union. --Publisher's description
Keywords: Arbitrators, Industrial; Communist Party of Canada; Labor leaders; Political activists; United Electrical, Radio and Machine Workers of America; Walsh, Bill, 1910-2004

Gustave Francq : figure marquante du syndicalisme et précurseur de la FTQ - Leroux, Eric (VLB, 2001)
Intellectuel du mouvement ouvrier, Gustave Francq (1871-1952) a suivi une carrière hors de l’ordinaire. Il a occupé une place dans les hautes sphères décisionnelles du mouvement syndical nord-américain pendant plus de quarante ans. Sa contribution à la mise sur pied de la Fédération provinciale du travail du Québec fait de lui un précurseur de la Fédération des travailleurs et des travailleuses du Québec (FTQ). À ce sujet, soulignons qu’il est le fondateur du journal Le Monde ouvrier, aujourd’hui l’organe officiel de la FTQ. --Résumé de l'éditeur
Keywords: Francq, Gustave, 1871-1952

Getting By in Hard Times: Gendered Labour at Home and on the Job - Luxton, Meg; Corman, June Shirley (University of Toronto Press, 2001)
[D]escribes the experiences of daily life for predominantly white, working class women and men during the period of "economic restructuring" begun in the 1980s. Luxton and Corman show how the shift from a pattern where women were full-time housewives and men were income earners, to one where women are increasingly income earners as well, is altering the experience of everyday life Based on a case study conducted from 1980 to 1996, of households where one person was employed at Stelco's manufacturing plant in Hamilton, Ontario, the book examines how working class families make a living by combining paid employment and unpaid domestic labour. During this period of government cutbacks the loss of secure employment for men (as the steel plant cut its labour force by about two-thirds), combined with women's increasing participation in the labour force, resulted in lower standards of living, reduced income, and the imposition of more unpaid work on family households. [The book] examines how growing insecurities undermined class politics while increasing gender, racial, and ethnic tensions. By focusing on the daily coping strategies of white working class women and men, the book shows the human face of changing gender, race, and class politics in Canada. --Publisher's description.
Keywords: Attitudes; Case studies; Class consciousness; Hamilton, Ontario; Iron and steel workers; Sex role; Working class

Remember Kirkland Lake: The Gold Miners' Strike of 1941-42 - MacDowell, Laurel Sefton (Canadian Scholars' Press, 2001)
[This book] tells the story of one of the most important industrial disputes in Canadian labour history. This strike united the Canadian labour movement around the demand for collective bargaining legislation, which it won in 1944 and which remains central to our industrial relations system. The book provides a comprehensive analysis of all the factors in this dramatic dispute. At the community level, a social history approach examines the local living and working conditions of the miners and their families, the role of the women in the dispute, and the ethnic makeup of the workforce. -- Publisher's description
Keywords: Canada; Gold Miners' Strike, Kirkland Lake, Ont., 1941-1942. Collective bargaining; History; Mining industry

Renegade Lawyer: The Life of J.l. Cohen - MacDowell, Laurel Sefton (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2001)
J.L. Cohen, one of the first specialists in labour law and an architect of the Canadian industrial relations system, was a formidable advocate in the 1930s and 1940s on behalf of working people. A 'radical lawyer' in the tradition of the great American counsel Clarence Darrow or contemporary advocate Thomas Berger who represent the less powerful and seek to reform society and to protect civil liberties, Cohen was also a 'labour intellectual' in Canada, similar to those supporting Roosevelt's New Deal in the United States. He wrote Collective Bargaining in Canada, served on the National War Labour Board, and advised the Ontario government about policy issues such as mothers' allowances, unemployment insurance legislation, and labour law..

Beyond Service: State Workers, Public Policy, and the Prospects for Democratic Administration - McElligott, Greg (Institute of Public Administration of Canada series in public management and governance, 2001)
This study concerns one department of Canadian government - Employment and Immigration Canada (EIC) - and one policy field - labour market policy - from 1976 to 1991. McElligott unearths resistance in workplaces where 'cutting edge' neoconservative managers have been trying to reshape government services, and inserts front-line workers into state theories, policy debates, and progressive political strategies. He argues that the neglect of these workers makes key state theories incomplete and separates policy-making theory - and practice - from actual state outputs. One consequence is that progressive thinkers and activists have forgone many promising strategic opportunities." "Beyond Service challenges current trends in administrative theory and policy-making, and will be of interest to academics, policy research bodies, union researchers, educators, and, most important, front-line government workers themselves. --Publisher's description
Keywords: Angestellter; Canada; Canada. Emploi et immigration Canada (Ministère) Fonctionnaires Cas, Études de; Canada. Employment and Immigration Canada (Department); Canada. Employment and Immigration Canada (Department) Officials and employees Case studies; Case studies; Civil service; Civil service Canada; Employee-management relations in government; Employee-management relations in government Canada; Employees; Fonction publique Canada; Fonction publique Relations de travail Canada; Kanada Government; Management Employee participation; Management Employee participation Canada; Personalpolitik; Personnel Participation à la gestion Canada; Verwaltung; Études de cas

The Tyranny of Work: Alienation and the Labour Process - Rinehart, James W. (Harcourt Canada, 2001)
The Tyranny of Work examines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. Completely updated to reflect current trends in the labour force and research in the field of labour studies, The Tyranny of Work begins with a thorough discussion of work as a social problem and the sources of alienation. The book then examines the development of industrial capitalism in Canada, the white-collar and blue-collar worlds, and, finally, solutions to the problem of alienated labour. All statistics and data have been updated to reflect the most current research. Information from the 2001 Census has been integrated throughout the text. The Tyranny of Work examines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. --Publisher's description, 5th edition (2005).Contents: 1. Work as a social problem -- 2. Alienation and its sources -- 3. Alienation and the development of industrial capitalism in Canada -- 4. Post-industrial society and white-collar worlds -- 5. Blue-collar crime -- 6. Restructuring organizations and work -- 7. Solutions to alienated labour. Includes bibliographical references (pages 218-245) and index;
Keywords: Labor -- Canada

Montmorency : histoire d'une communauté ouvrière - Simard, Jean-François (Septentrion, 2001)
Voici une fresque émouvante de la vie des gens attachants qui ont fait au fil des siècles l’histoire touchante de cette petite ville dont le site naturel du " Sault de Montmorency ", comme l’avait baptisé Champlain, est connu de tous. Le syndicaliste Fernand Daoust, qui rédige la préface de cet ouvrage, n’hésite pas à affirmer que " Jean-François Simard, par un remarquable travail de recherche minutieuse et parfois inédite, brosse un saisissant tableau d’une petite société qui souffre, qui peine mais qui rêve aussi tout au long de ses inépuisables générations […] ". Ballottés du monde rural au monde industriel puis postindustriel, les gens de Montmorency ont développé une conscience sociale qui a marqué la lutte des travailleurs québécois. En rappelant les péripéties de ces bouleversements, Jean-François Simard nous convie à un devoir de mémoire, d’attachement et de reconnaissance envers un petit coin attachant du Québec dont le labeur et le sens des responsabilités de ses habitants ont contribué à forger l’identité d’un peuple et à perpétuer ses valeurs d’endurance et de solidarité. L’histoire des femmes et des hommes qui ont vécu à Montmorency fait partie de notre patrimoine collectif et appartient à tout le Québec. Cet ouvrage s’intéresse donc à l’essor puis au déclin d’une petite communauté ouvrière, patrie de Fernand Dumont qui s’en est grandement inspiré pour ses travaux. Cette communauté, dans sa relation au double mouvement d’industrialisation et de désindustrialisation qui a rythmé l’avènement du capitalisme au cours du dernier siècle, a marqué de manière indélébile la quête des ouvriers québécois pour une plus grande justice sociale. --Résumé de l'éditeur
Keywords: Classe ouvrière; Condition sociale; Condition économique; Développement économique régional; Histoire; History; Industrie Québec (Province) Montmorency (Beauport) Histoire; Industries; Industries Québec (Province) Montmorency (Beauport) History; Montmorency (Beauport, Québec); Montmorency (Beauport, Québec) Conditions sociales; Montmorency (Beauport, Québec) Histoire; Montmorency (Beauport, Québec) History; Montmorency (Beauport, Québec) Social conditions; Ouvrier; Québec (Canada; province) Conditions sociales; Social conditions; Sociologie rurale; Syndicalism; Syndicalism Québec (Province) Montmorency (Beauport) History; Syndicalisme Québec (Province) Montmorency (Beauport) Histoire; Travail

Public-Sector Labour Relations in an Era of Restraint and Restructuring - Swimmer, Gene; Rose, Joseph B.; Wagar, Terry H.; Philips, Paul; Stecher, Carolina; Reshef, Yonatan; Thompson, Mark; Bach, Sandra; Adams, Roy J. (Oxford University Press, 2001)
The 1990s in Canada will probably go down as the most stressful decade for public-sector industrial relations since the inception, 25 years earlier, of collective bargaining in the public service. Government debt and defecits became the rationale for downsizing, outsourcing, privatization, layoffs, buyouts, and early retirement packages at both the federal and provincial levels. When workers' bargaining units did not bend to government demands at the negotating table, and when leaders did not blink at the threat of restrictive legislation, then governments of both the right and the left at times found it convenient to legislate rule changes to suit their fiscal or ideological purposes. The contributors to Public-Sector Labour Relations examine in depth the events of recent years in the public service of six jurisdictions―Nova Scotia, Ontario, Manitoba, Alberta, British Columbia, and the federal government. Trends in the other five Canadian provinces are also considered. Only in BC has there been an essentially co-operative labour relations environment, although even in this province, public service employment has dropped considerably. Overall, from 1991 to 1997, provincial civil service employment fell by 15 per cent, while the federal employment reduction was 14 per cent. (From the employment peak in 1993-4, the overall provincial reduction was over 22 per cent.) Although collective bargaining is still alive, a major conclusion of this study is that collective bargaining in the Canadian public sector is not well. The cases reported here demonstrate that governments have adopted the attitude and policy that they may engage in bargaining or suspend it whenever they find that course of action to be convenient. Viewed from a broader international context, as discussed in the concluding chapter, the casual suspension of bargaining by Canadian governments cannot be justified by the norms and agreements that Canada has shared with the international community. -- Publisher's description. Contents: Public-sector labour relations in an era of restraint and restructuring: an overview / Gene Swimmer -- Provincial government restructuring in Nova Scotia: the freezing and thawing of labour relations / Terry H. Wagar -- From softball to hardball: the transition in labour-management relations in the Ontario public service / Joseph B. Rose -- Fiscal restraint, legislated concessions, and labour relations in the Manitoba civil service, 1988-1997 / Paul Phillips and Carolina Stecher -- The logic of union quiescence: the Alberta case / Yonatan Reshef -- Labour relations in the BC public service: blowing in the political wind / Mark Thompson -- Restructuring federal public-sector human resources / Gene Swimmer and Sandra Bach -- Public-employee relations: Canadian developments in perspective / Roy J. Adams.

Union Learning: Canadian Labour Education in the Twentieth Century - Taylor, Jeffery M. (Thompson Educational, 2001)
Over 100,000 Canadian workers participate annually in educational programs conducted by their union or the broader labour organizations to which their union belongs. Union-based education is the most significant nonvocational education available to working people. This activity has been going on for decades, and Jeffery Taylor's Union Learning: Canadian Labour Education in the Twentieth Century is the first comprehensive history of it. Union Learning chronicles the rise and decline of the Workers' Educational Association, the development of internal union educational programs, the consolidation of the Canadian Labour Congress's educational system after 1956, the origin and growth of the Labour College of Canada, and the patchy history of university and college involvement in labour education. Taylor argues that a new emphasis on broad-based and activist education today promises to rekindle the sense of an educational movement that was present in the labour movement in the 1930s and 1940s. The book includes a number of illustrative sidebars and photographs. --Publisher's description
Keywords: 20th century; Canada; Education History; History; Labor unions and education; Working class

A Fishery for Modern Times: The State and the Industrialization of the Newfoundland Fishery, 1934-1968 - Wright, Miriam (Canadian social history series, 2001)
In the early 1990s, the northern cod populations off the coast of Newfoundland had become so depleted that the federal government placed a moratorium on commercial fishing. The impact was devastating, both for Newfoundland's economy and for local fishing communities. Today, although this natural resource exploited commercially for over 500 years appears to be returning in diminished numbers, many fisheries scientists and fishers question whether the cod will ever return to its former abundance. In A Fishery for Modern Times, Miriam Wright argues that the recent troubles in the fishery can be more fully understood by examining the rise of the industrial fishery in the mid-twentieth century. The introduction of new harvesting technologies and the emergence of 'quick freezing', in the late 1930s, eventually supplanted household production by Newfoundland's fishing families. While the new technologies increased the amount of fish caught in the northwest Atlantic, Wright argues that the state played a critical role in fostering and financing the industrial frozen fish sector. Many bureaucrats and politicians, including Newfoundland's premier, Joseph Smallwood, believed that making the Newfoundland fishery 'modern', with centralization, technology, and expertise, would transform rural society, solving deep-seated economic and social problems. A Fishery for Modern Times examines the ways in which the state, ideologies of development, and political, economic, and social factors, along with political actors and fishing company owners, contributed to the expansion of the industrial fishery from the 1930s through the 1960s. While the promised prosperity never fully materialized, the continuing reliance on approaches favouring high-tech, big capital solutions put increasing pressure on cod populations in the years that followed. As Wright concludes, 'We can no longer afford to view the fisheries resources as 'property' of the state and industry, to do with it as they choose. That path had led only to devastation of the resource, economic instability, and great social upheaval." --Publisher's description